(untitled) (Journal of Science and Technology, 2016)
The effects of collar diameter and lifting period on shoot biomass production of Teak (Tectona grandis Linn. F) stumps were investigated during the 2006 dry season on the research farm of Kwame Nkrumah University of Science and Technology, Kumasi, Ghana. The lifting period is time when planting of stumps is delayed. A 3x5 split-plot factorial experiment in randomized complete block design was used. The main aim was to determine suitable methods of converting teak seedlings into stumps and evaluate the consequences of delaying planting of teak stumps to enhance high amount of teak shoot production thus address the persistent problem of poor sprouting and low biomass productivity in the early stages of planted teak in large-scale plantation development in Ghana. Collar diameter of stumps, and time as well as the interaction of collar diameter and period of delay of planting stumps and the combined effects of these factors had significant effect on number of shoots per plot. The highest number of teak shoots was obtained from teak stumps of collar diameter of 2.75 cm planted immediately after harvesting. For teak stumps of collar diameter of 2.75 cm if planting is delayed for 4 weeks the number of shoots reduces to 25 % of its value if planted immediately. Teak stumps stored in the open air when planting is delayed beyond 15 weeks may not produce shoots.